A Multimodal Hybrid Piezoelectric–Electromagnetic Vibration Energy Harvester Exploiting the First and Second Resonance Modes for Broadband Low-Frequency Applications - Shishkovski, Dejan; Petreski, Zlatko; Markovska, Simona Domazetovska; Anachkova, Maja; Pecioski, Damjan; Ignjatovska, Anastasija Angjusheva (MDPI AG, 2026)
The increasing demand for autonomous wireless sensors in Internet of Things (IoT) ap-plications has intensified research on vibration energy harvesting, particularly in the low-frequency range where ambient vibrations are most prevalent. However, most vibra-tion energy harvesters operate efficiently only at a single resonance mode, resulting in a narrow operational bandwidth and pronounced performance degradation under fre-quency detuning. To address this limitation, this paper proposes a multimodal hybrid pi-ezoelectric–electromagnetic vibration energy harvester that exploits both the first and sec-ond resonance modes of a cantilever-based structure to achieve broadband low-frequency operation. The design is guided by the complementary utilization of strain-dominated and velocity-dominated regions associated with different vibration modes. Numerical model-ing and finite element simulations are employed to investigate the influence of mass dis-tribution, deformation characteristics, and relative velocity on energy conversion perfor-mance. A secondary cantilever carrying the electromagnetic coil is introduced to enhance the relative motion between the coil and the magnetic field, thereby extending the effective operational bandwidth. The experimental results demonstrate increased harvested power, improved energy conversion efficiency, and a significantly broadened effective frequency range compared to conventional single-mode piezoelectric and electromagnetic energy harvesters.
Keywords: energy harvesting; hybrid piezoelectric–electromagnetic harvester; multimodal resonance; broadband operation